EMPLOYING A SIMULATION MODEL TO EVALUATE THE PERFORMANCE OF THE PRODUCTION SYSTEM DIVISION IN THE MATERIAL REQUIREMENTS PLANNING (MRP) SYSTEM - Mohammad Turki Abdul-Abbas (Scholars Digest Publishing, 2024)
The research aims to investigate the strategy for allocating mechanics of the production system consisting of materials subjected to Material Requirements Planning (MRP) system control byperformance evaluations whose components are: inventory costs, late order costs and the level of services. The research problem is mainly centred ondetermining the best model that achieves MRP based on its peculiarities as a model with complex requirements. This is because figuring out the optimal production technique and breaking the production system down into its component parts are necessary steps in the planning process. Similarly, the strategy applies to thecombinations of machines available for both types of materials. Likewise, the simulation model can equally be used on the developable production plan, which was prepared by determining the landmarks of the specific database without specific work execution by the model. On the high preparation times anda low number of elements, the research found that whenever the production system utilization is higher, the policy of fragmentation or division of the production system will be better. However, the The optimal machine combinations for medium and low utilisation levels are accessible across all versions. Additional research in operations management benefits from the scalable simulation model for many production system types.